XPO1 regulates erythroid differentiation and is a new target for the treatment of β-thalassemia - Guillem, Flavia; Dussiot, Michaël; Colin, Elia; Suriyun, Thunwarat; Arlet, Jean Benoit; Goudin, Nicolas; Marcion, Guillaume; Seigneuric, Renaud; Causse, Sebastien; Gonin, Patrick; Gastou, Marc; Deloger, Marc; et al. (Haematologica, 2020)
β-thalassemia major (β-TM) is an inherited hemoglobinopathy caused by a quantitative defect in the synthesis of β-globin chains of hemoglobin, leading to the accumulation of free a-globin chains that aggregate and cause ineffective erythropoiesis. We have previously demonstrated that terminal erythroid maturation requires a transient activation of caspase-3 and that the chaperone Heat Shock Protein 70 (HSP70) accumulates in the nucleus to protect GATA-1 transcription factor from caspase-3 cleavage. This nuclear accumulation of HSP70 is inhibited in human β-TM erythroblasts due to HSP70 sequestration in the cytoplasm by free a-globin chains, resulting in maturation arrest and apoptosis. Likewise, terminal maturation can be restored by transduction of a nuclear-targeted HSP70 mutant. Here we demonstrate that in normal erythroid progenitors, HSP70 localization is regulated by the exportin-1 (XPO1), and that treatment of β-thalassemic erythroblasts with an XPO1 inhibitor increased the amount of nuclear HSP70, rescued GATA-1 expression and improved terminal differentiation, thus representing a new therapeutic option to ameliorate ineffective erythropoiesis of β-TM.